Is endovascular treatment still good for acute ischemic stroke in the elderly? A meta-analysis of observational studies in the last decade - Jiang, Xin; Wang, Jian; Hu, Yaowen; Lang, Hui; Bao, Jiajia; Chen, Ning; He, Li (Frontiers in Neuroscience, 2024)
The lack of randomized evidence makes it difficult to establish reliable treatment recommendations for endovascular treatment (EVT) in elderly patients. This meta-analysisstudy aims to evaluatemake a direct comparison of the therapeutic effects of endovascular treatment for acute ischemic stroke in the elderly compared with younger patients.Comprehensive literature retrieval was conducted to identify studies that directly compared the outcomes of EVT in elderly patients and those aged ˂80 years. The primary outcome was functional independenceoutcome at 90 days, defined as mRS 0-2 at 90 days after EVT. The secondary outcomes were the rate of successful recanalization, symptomatic intracranial hemorrhage (sICH) and mortality.Odds ratios (ORs) were estimated using a random effects model.In total, twenty-six studies with 9492 enrolled participants were identified. Our results showed that, compared with patients aged ˂80 years undergoing EVT, EVT was associated with a lower rate of functional independence at 90 days (OR = 0.38; 95% CI, 0.33-0.45; P <0.00001) and a higher mortality 2 rate (OR = 2.51; 95% CI, 1.98-3.18; P <0.00001) in the elderly. Furthermore, even without a significantly observed increase in sICH (OR = 1.19; 95% CI, 0.96-1.47; P =0.11), EVT appeared to be associated with a lower rate of successful recanalization (OR = 0.81; 95% CI, 0.68-0.96; P =0.02).Evidence from observational studies revealed that EVT has less functional outcomes in elderly patients with acute ischemic stroke. Further studies are needed to better identify patients aged ≥80 years who could potentially benefit from EVT.